Quinolin-4-ones: Methods of Synthesis and Application in Medicine - Katarzyna Gach-Janczak; Justyna Piekielna-Ciesielska; Jakub Waśkiewicz; Kamil Krakowiak; Karol Wtorek; Anna Janecka (Molecules)
Quinolinones, also called quinolones, are a group of heterocyclic compounds with a broad spectrum of biological activities. These compounds occur naturally in plants and microorganisms but can also be obtained synthetically. The first synthesis of quinolinones took place at the end of the 19th century, and the most recent methods were published just a few years ago. They allow for obtaining an unlimited number of analogs differing in biological properties. In this review, we described the plethora of methods leading to quinolin-4-ones. Several of these compounds have been used as antibiotics for over four decades, but recently, their antiproliferative effects have been of particular interest to researchers. This review summarizes the experimental progress made in the synthetic development of various routes leading to quinoline-4-ones and presents an overview of the structures, their evolution, and their relation to activity.